Land fragmentation effects on technical efficiency of cassava farmers in South-West geopolitical zone, Nigeria - Balogun, O. L. (Cogent social sciences, 2017)
This paper provides regional effects of land fragmentation on technical efficiency of 462 cassava farmers selected through a multitage sampling technique from South-West geopolitical zone of Nigeria. The analysis was based on cassava farmers’ 2015/2016 production season data, using the stochastic production frontier model. Mean farm holdings and plots size per farmer in the study area were 2.37 and 1.075 ha respectively. Results show that quantity of labour used, land size and quantity of planting material are influential determinants of technical efficiency of cassava farmers. The result further revealed that fragmentation index and distance between farm and farmstead are the only significant technical inefficiency variables. The study found that substantial technical inefficiency exists in cassava farming. The study recommends land reforms that directly targeted at cassava farmers in form of enhancement progamme to increase their production efficiency.